Field monitoring and numerical simulation of the thermal actions of a supertall structure. Issue 4 (23rd June 2016) - Su, Jia‐zhan; Xia, Yong; Ni, Yi‐qing; Zhou, Lin‐ren; Su, Cheng
Summary: Structural temperature is an important loading that must be considered during the design, construction, and safety assessment. The thermal action of supertall structures has rarely been investigated because of insufficient real measurement data, as compared with that on bridges. In this study, the thermal action of the 600‐m‐tall Canton Tower is investigated on the basis of the comprehensive long‐term SHM system installed on the structure and the numerical simulation. First, the temperature model of the entire structure is derived by using the field monitoring and numerical heat transfer analysis data. In particular, (i) the temperature difference between different facades of the inner tube, (ii) the temperature difference profile of the outer tube, and (iii) the distribution of the temperature difference between the inner and outer tubes along the structural height are presented in detail. Results show that the nonuniform distribution of the temperature field between the different components of the structure is significant and should be carefully considered in the analysis of such a complex supertall structure. Second, the temperature effects on structural displacement, stress, and internal forces consisting of (i) the tower top horizontal displacement during different seasons, (ii) the stresses of different levels/components, and (iii) the bending moments/shear forces along the structural height are investigated. The simulated results obtained by using the global finite element model of the tower are verified through a comparison with the measurements. This study provides first‐hand data for the design of supertall structures in the tropical region of China. Copyright © 2016 John Wiley & Sons, Ltd.